Comparison of the Qualitative Chemical Composition of Extracts from Ageratina havanensis Collected in Two Different Phenological Stages by FIA-ESI-IT-MSn and UPLC/ESI-MSn: Antiviral Activity - Garcia, Trina H.; Quintino da Rocha, Claudia [UNESP]; Dias, Marcelo J. [UNESP]; Pino, Liudis L.; del Barrio, Gloria; Roque, Annele; Perez, Caridad E.; Campaner dos Santos, Lourdes [UNESP]; Spengler, Iraida; Vilegas, Wagner [UNESP] (Natural Products Inc, 2017)
The flowers and leaves of Ageratina. havanensis (Kunth) R. M. King & H. Robinson are traditionally used as a tea to cure several diseases. The production of active secondary metabolites can be affected by several environmental factors such as climate, altitude, rainfall, phenological stage and other conditions that may influence the growth of plants. In this sense, the development of a methodology to compare the chemical composition of plant extracts is needed. The qualitative chemical composition of the ethyl acetate extracts of flowers and leaves, collected in both reproductive and non-reproductive season, was determined by flow injection analysis-electrospray ionization-ion trap tandem mass spectrometry (FIA-ESI-IT-MSn) and ultra-high-performance liquid chromatography coupled to electrospray negative ionization mass spectrometry (UPLC/ESI-MSn). The qualitative chemical composition of the ethyl acetate extracts of flowers and leaves was very similar in all cases. Also the antiviral activity of flowers against human herpes simplex viruses type 1 and 2 (HSV-1, HSV-2) (Herpesviridae) was analyzed. Three glucoside flavonoids were isolated from the ethyl acetate extract of the leaves of A. havanensis collected in flowering season using chromatographic methods and their structures were elucidated by physical and spectroscopic data measurements, and by comparing the obtained data with previously published values. The compounds were identified as 5-O-beta-D-glucosy1-7-methoxyaromadendrin (5), 7-O-beta-D-glucosy1-4'-dihydroxy-5-methoxyfiavanone (6) and 5-O-beta-D-glucosylsakuranetin (7); this is the first report of the isolation of these compounds in the Asteraceae family. Since the qualitative composition of the extracts of A. havanensis was similar in all cases, it can be expected that the ethyl acetate extract of the leaves collected in the non-reproductive season has anti-herpetic activity similar to that obtained in the reproductive season.
Keywords: Ageratina havanensis; Flavonoids; Tandem mass spectrometry; Anti-herpetic activity